The chemical behaviors of microplastics in marine environment: A review. (May 2019) - Guo, Xuan; Wang, Jianlong
Abstract: Microplastics are widely existed in marine and coastal environments, which aroused global concern in recent years. This review mainly summarized the interactions of organic pollutants and metals with microplastics based on environmental monitoring results and laboratory results reported by literatures. Firstly, the type, properties, and distribution of microplastics in the environment were briefly reviewed. Secondly, the property changes of microplastics after degradation were discussed. Thirdly, the concentrations of pollutants on microplastics in global environments were summarized. Then the effect of the factors (e.g. types and properties of microplastics, types of pollutants, and environmental conditions) on the sorption behaviors of microplastics were discussed in detail. Finally, the influences of microplastics on marine organisms were briefly evaluated. Graphical abstract: Unlabelled Image Highlights: Microplastics are emerging pollutants ubiquitous in marine and coastal environments. This paper mainly reviewed the chemical behaviors of microplastics in environments. The types, properties and distributions of microplastics were introduced. Their property changes after degradation in the environment were discussed. The concentrations of pollutants onto microplastics were analyzed and summarized.